The use of high-resolution satellite imagery in forest inventory : a case of Hans Kanyinga Community Forest - Namibia - Kamwi, Jonathan Mutau (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Forest and Wood Science))—University of Stellenbosch, 2007.